Incidence and predictors of readmissions to non-index hospitals after transcatheter aortic valve replacement and the impact on in-hospital outcomes: From the nationwide readmission database. (1st October 2019) - Ando, Tomo; Adegbala, Oluwole; Villablanca, Pedro; Akintoye, Emmanuel; Ashraf, Said; Shokr, Mohamed; Siddiqui, Fayez; Takagi, Hisato; Grines, Cindy L.; Afonso, Luis; Briasoulis, Alexandros
Abstract: Introduction: Whether readmission to non-index hospitals (where the initial procedure was not performed) could result in adverse outcomes and increased utilization of healthcare resources compared with readmission to index hospitals after transcatheter aortic valve replacement (TAVR) remains unclear. Methods: From January 2012 to September 2015, a nationwide readmission database was queried to identify those who were older than 50 years and had endovascular TAVR, using the International Classification of Disease, 9th Revision, Clinical Modification code 35.05. Elective readmissions were excluded. In-hospital outcomes were compared between the index and non-index hospital readmissions. A multivariable logistic regression analysis was performed to identify predictors of non-index hospital readmissions. Results: A total of 6808 readmissions were identified of which 2564 (37.7%) were readmitted to non-index hospitals. Residents at smaller counties, metropolitan non-teaching hospitals, or hospitals at large metropolitan areas were predictors of non-index readmissions. In-hospital mortality (adjusted odds ratio [aOR] 1.27, p = 0.20), acute myocardial infarction (aOR 0.83, p = 0.53), pacemaker placement (aOR 0.97, p = 0.90), acute kidney injury (aOR 0.98, p = 0.84), and stroke (aOR 1.03, p = 0.90) were similar between index and non-index readmissions but bleeding events requiring transfusions were more frequently observed in readmissions at non-index hospitals (aOR 1.32, p = 0.025). Hospital cost (15, 410 dollars vs. 16, 390 dollars, p = 0.25) and length of stay (5.70 days vs. 5.65 days, p = 0.85) were comparable between groups. Conclusions: Non-index readmissions post-TAVR was relatively common but did not result in increased hospital mortality or healthcare utilization. Our results are reassuring for TAVR recipients with limited access to index hospitals. Highlights: Non-index hospital readmissions were common post-TAVR, at 37.7%. Outcomes and cost were mostly similar between index versus non-index readmission. These findings are reassuring for those with limited access to index hospitals.